Will ChatGPT bring a New Paradigm to HR World? A Critical Opinion Article - Ifta Firdausa Nuzula; Muhammad Miftahul Amri (The Indonesian Institute of Science and Technology Research, 2023)
Since ChatGPT was first publicly available in November 2022, it has sparked attention worldwide. Some believe that ChatGPT might revolutionize our lives. There have been interesting discussions surrounding ChatGPT. In this chance, we explore the potential use of ChatGPT in the HR industry. For HR managers, the use of AI in HR has traditionally been limited to simple tasks, but ChatGPT's ability to understand and respond to natural language input opens up new possibilities for automating more complex HR tasks such as interviewing and onboarding. On the other side, ChatGPT can also help job seekers to get their dream jobs. To begin with, ChatGPT can be employed to find out the benefits and working environment in a specific company, although it should be noted that ChatGPT's answers cannot be blindly trusted. ChatGPT can also prepare a cover letter, a motivation letter, an application email, etc. Job seekers can even ask ChatGPT to act as an interviewer in an interview mockup. We present ChatGPT utilization examples in the HR world. In this article, we also conducted a mini experiment to investigate whether, in its current state, ChatGPT can generate a convincing cover letter that is able to fool HR specialists. The results showed that among the 5 study participants, none of them were able to correctly guess all of the letters, with the average correct answers of only 2 of 4 cover letters. Lastly, we also discuss the potential benefits and challenges of using ChatGPT in the HR industry in this article. Nevertheless, we argue that ChatGPT introduces a HR world’s paradigm shift.